Indonesia Composite Index and Market Reaction in Indonesia Due to Covid-19 Pandemic - Widnyana, I Wayan; Warmana, G Oka (APMBA (Asia Pacific Management and Business Application), 2022)
This study aims to examine the impact of the Covid-19 pandemic on the Indonesia Composite Index (ICI) and the reaction of the Indonesian capital market to events related to the Covid-19 pandemic in Indonesia. There were two events observed, the first event was the announcement of the first positive case of Covid-19 in Indonesia, and the second event was the determination of the status of a national disaster by the Indonesian government. Testing of effect of the Covid19 pandemic on stock prices was carried out by using an independent sample t-test against the average ICI before and after the two events. Testing the market reaction using the event study methodology. The test results found that the ICI average decreased significantly after the announcement of the first positive Covid-19 case. The ICI average also decreased significantly after the determination of the national disaster status. The average ICI return did not differ significantly before and after the two events. The market reaction test found no significant abnormal returns around the two events. The Covid-19 pandemic had an impact on the Indonesian capital market, marked by a decline in the ICI, although investors in the capital market did not react excessively, so there was no significant abnormal return.